2010
DOI: 10.1016/j.sdentj.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Dental patients’ awareness and knowledge in using dental implants as an option in replacing missing teeth: A survey in Riyadh, Saudi Arabia

Abstract: The results of this survey showed an acceptable level of awareness about dental implants among a selected sample of dental patients in Riyadh. It also showed the need for providing more general and accurate information to the patients about this treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
50
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 14 publications
14
50
7
Order By: Relevance
“…The present distribution of information sources resembles those reported by Pommer et al12 However, Berge10 reported news media, and Al-Johany17 reported friends and their relatives as the main source of information. About 68% of the interviewed population wished to have more information about dental implants and the 77% of them preferred to get this information from their dentist in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The present distribution of information sources resembles those reported by Pommer et al12 However, Berge10 reported news media, and Al-Johany17 reported friends and their relatives as the main source of information. About 68% of the interviewed population wished to have more information about dental implants and the 77% of them preferred to get this information from their dentist in this study.…”
Section: Discussionsupporting
confidence: 86%
“…DIs are increasingly used in the prosthetic treatment of edentulous patients to improve denture retention, stability, and functionality, thereby affecting the oral health‐related QoL . This statement is supported by Grogono et al, who reported that 88% of the individuals studied had an increase in self‐confidence after implant treatment, 89% would accept implant procedure treatments again, and 98% stated that their oral health had generally improved .…”
Section: Discussionmentioning
confidence: 84%
“…The level of knowledge and awareness of DIs and implant treatment varies among several studies performed in different countries . Public awareness, positive attitude, and the acceptance of DIs were found to be high in a study conducted by Zimmer et al in America, while a low level of awareness about DI treatment was found among patients in Finland .…”
mentioning
confidence: 94%
“…Unfortunately, the same cannot be said of developing countries with poorer access to dental care, where different authors[891011] have reported wide variability in the acceptance of this newer option of tooth replacement. In our setting, a resource-challenged environment, conservative dentistry is relatively young and there is dearth of information regarding patients’ knowledge of tooth replacement as a whole and the use of implant-retained prostheses as an option of replacement of missing tooth.…”
Section: Introductionmentioning
confidence: 99%